Sila i slabostʹ Reformacii v Vostočnoj Evrope - Bokun, Antoni (Bogoslovskie razmyšlenija, 2016)
This paper reviews the causes of the spread of the Reformation in Eastern Europe, as well as the reasons for its fall at the end of the XVI century. Reformation movement in Eastern Europe to successfully compete with the Catholic and the Orthodox Churches in the region thanks to the attractive ideological and intellectual program, as well as through the number of active and influential leaders. However, faced with renewed Catholicism, the reformers lost the conquered positions due to shortcomings in education and propaganda their ideas, as well as the lack of attention to the preparation of the ministers and the development of national culture.